Full-service restaurant leaders' preparedness for managing employee mental health issues post COVID-19. Issue 1 (7th March 2022) - McAdams, Bruce; Gallant, Monica
Abstract: Anecdotal evidence suggests that restaurant leaders are not prepared to deal with the mental health issues of their employees. A total of 20 leaders of restaurants were interviewed to address the implications of this question: "Is there a gap between mental health support needed for restaurant workers and the preparedness of their leaders and organizations?" Findings suggest restaurant leaders believe dealing with employee mental health issues is an increasingly significant part of their job, especially with the onset of the COVID-19. While there is a varying range of leader preparedness to deal with these issues, restaurants as organizations seem unprepared.